2001
DOI: 10.1093/carcin/22.9.1465
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in the production of a `bystander signal' following irradiation of primary cultures of normal human urothelium

Abstract: The existence of a bystander effect following both alpha and gamma irradiation of many cell lines is not now in dispute. The significance of this effect for cancer risk assessment and radiotherapy treatment planning requires demonstration of its relevance in vivo. The problem in demonstrating the existence of the effect in vivo is that other systemic effects may mask or confound the effect being investigated and it is practically impossible to attribute an effect in a particular cell to a signal produced in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 21 publications
1
70
0
Order By: Relevance
“…It has been demonstrated that gap-junction-mediated communication in human bladder explant outgrowth depends on a smoking status of the tissue donors (Lyng et al, 1996). Also, other studies have reported a relationship between the level of bystander signal produced and gender and malignancy status (Mothersill et al, 2001). Further studies in defined populations using the model described here would clearly be useful to clarify the variations in response we have observed.…”
Section: Discussionmentioning
confidence: 55%
“…It has been demonstrated that gap-junction-mediated communication in human bladder explant outgrowth depends on a smoking status of the tissue donors (Lyng et al, 1996). Also, other studies have reported a relationship between the level of bystander signal produced and gender and malignancy status (Mothersill et al, 2001). Further studies in defined populations using the model described here would clearly be useful to clarify the variations in response we have observed.…”
Section: Discussionmentioning
confidence: 55%
“…The promitogenic response was attributed to increases in the concentrations of a cytokine (TGF-b1) in cell supernatants; a concentration that also induced intracellular ROS in unirradiated cells and, unlike the gap-junction-mediated mechanism in skin fibroblasts (Azzam et al, 2001), led to decreased cellular levels of CDKN1A/p21 and also p53 (Iyer and Lehnert, 2000). Potentially related to the mechanisms mediating cytogenetic damage not requiring gap-junctional communication is the finding that the medium in which certain cells have been irradiated contains an activity, probably a protein, that produces cytotoxic effects in nonirradiated cells Lyng et al, 2000Lyng et al, , 2002Mothersill et al, 2000bMothersill et al, , 2001Seymour and Mothersill, 2000). The first detectable effect of the medium containing the cytotoxic activity on recipient cells is a rapid (1-2 min) calcium pulse followed 30 min-2 h later by changes in mitochondrial membrane permeability and the induction of ROS (Lyng et al, 2000(Lyng et al, , 2002; a role for mitochondrial metabolism is suggested by the lack of signal production by cells that lacked functional glucose-6-phosphate dehydrogenase (Mothersill et al, 2000b).…”
Section: Mechanisms Underlying Radiation-induced Bystander Effectsmentioning
confidence: 99%
“…For confluent cell monolayers and 3-dimensional cell clusters, gap junctional intercellular communication (GJIC) has been found to play a critical role in radiation-induced bystander effects. [14][15][16][17][18] In other cases, soluble extracellular factors, including reactive oxygen species (ROS) and cytokines, [19][20][21] which are released from irradiated cells and even human tissue, 22 contribute to the bystander responses. We and others have found that radiation-induced nitric oxide (NO) has multiple bystander effects on non-irradiated cells.…”
mentioning
confidence: 99%